Mongols in Armenian Manuscript Sources of the 13th–14th Centuries - Artashes I. Shahnazaryan; Ashot A. Melkonyan; Igor V. Kryuchkov; Harutyun H. Khudanyan (Монголоведение)
Introduction. A significant amount of diverse and valuable information regarding the Mongols, who arrived in Armenia during their exploratory expeditions in 1220–1222 and governed the country from 1236 to 1353, has been preserved in Armenian manuscript sources. These sources contain detailed accounts of the Mongols’ names, origin, homeland, appearance, food, character, customs, beliefs, weaponry, martial arts, language, and overall ethnology. This collection of insights illuminates the historical significance due to the fact that Mongols played a pivotal role in global history. The scientific importance of this material should not be underestimated, particularly for Mongolian studies and Mongolian ethnology. This significance arises from both the variety of accounts in the Armenian manuscript sources and the reliability of the majority of these reports. Many of these accounts are based either on direct observations by the authors or the information obtained from credible sources, including the Mongols themselves. It is no coincidence that this emphasis on accuracy is regularly highlighted within the manuscript sources. The purpose of this study is aimed at bringing together and, for the first time, introducing into scientific circulation the ethnological material on the Mongols provided in the rich and valuable Armenian manuscript sources (historical works, minor chronicles, manuscript colophons) of the High Middle Ages (13th-14th centuries). Materials and methods. Among the Armenian manuscript sources addressing the ethnological characteristics of the Mongols, the historiographical works of such notable historians as Kirakos Gandzaketsi, Vardan Vardapet, Grigor Aknertsi, Smbat Sparapet, Hetum the Historian, and Stepanos Orbelian are particularly prominent. Several chroniclers and authors of manuscript colophons have echoed or even expanded upon the mentioned above accounts. The work on the Mongols by Vanakan Vardapet, the teacher of Kirakos Gandzaketsi, by Vardan Vardapet and by Grigor Aknertsi, also undoubtedly contained valuable insights into this subject. Unfortunately, this work has not survived, although Vardan Vardapet almost certainly drew upon it in his own writings. In some cases, Vardan Vardapet also compiled material about the Mongols from the works by Kirakos Gandzaketsi. The information related to the ethnology and lifestyle of the Mongols, as recorded in the Armenian sources of the High Middle Ages, is presented here through a combination of historical compilation and analytical methods for the reconstruction of the history. Results. The aforementioned evidence forms the basis for introducing the material from Armenian manuscript sources on Mongol ethnology into scientific discourse that will facilitate a deeper and more comprehensive understanding of the ethnological characteristics of the Mongols during the period in question.